Feasibility Analysis of Lobster (Panulirus sp) Aquaculture Business in The Pokdakan Gisman Jaya Group, Penajam Sub-District, Penajam Paser Utara Regency - Ilham , Mohammad Sahrul; Gunawan, Bambang Indratno; Abdusysyahid, Said (Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
The purpose of this study was to determine the feasibility of the business in lobster shrimp farming (Panulirus sp) and to determine the level of costs and profit levels of lobster shrimp farming (Panulirus sp) in the Pokdakan Gisman Jaya Group, Penajam District, North Penajam Paser Regency. The sampling method used in this study is the saturated sample method. Data analysis uses methods of production cost as well as profit analysis, business feasibility analysis and qualitative descriptive analysis using a likert scale. According to the results of the cost analysis incurred is IDR 26,921,133 respondent/production, profit is IDR.41.114.337/respondent/production, R/C value of 2.82, payback period of 0.654 times production.